BD750, a benzothiazole derivative, inhibits T cell proliferation by affecting the JAK3/STAT5 signalling pathway. (16th January 2013) - Liu, Y; Yang, T; Li, H; Li, M‐H; Liu, J; Wang, Y‐T; Yang, S‐X; Zheng, J; Luo, X‐Y; Lai, Y; Yang, P; Li, L‐M; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose A series of benzothiazole derivatives were screened for immunosuppressive activity; of these compounds BD750 was found to be the most effective immunosuppressant. The purpose of the current study was to determine the immunosuppressive activity of BD750 on T cell proliferation and its potential mode of action. Experimental Approach T cell proliferation, CD25 and CD69 expression and cell cycle distribution were measured in vitro by flow cytometry. Cell viability was determined by CCK‐8 assay. Cytokine levels were measured by elisa. The activation of signal‐regulated molecules was assessed by Western blot analysis. The effects of BD750 were evaluated in vivo in a mouse model of delayed‐type hypersensitivity. Key Results BD750 significantly inhibited mouse and human T cell proliferation, stimulated either by anti‐CD3/anti‐CD28 monoclonal antibodies or by an alloantigen, in a dose‐dependent manner in vitro. No obvious cytotoxic effects of BD750 were observed in our experimental conditions. Furthermore, BD750 did not inhibit CD25 and CD69 expression or IL‐2 and IL‐4 secretion, but induced cell cycle arrest at the G0/G1 phase in activated T cells. In IL‐2‐stimulated CTLL‐2 cells and primary activated T cells, BD750 inhibited cell proliferation and STAT5 phosphorylation, but not Akt or p70S6K phosphorylation. BD750 also reduced the T cell‐mediated delayed‐type hypersensitivity response in mice in a dose‐dependent manner. Conclusion and Implications These data indicate that BD750 inhibits IL‐2‐induced JAK3/STAT5‐dependent T cell proliferation. BD750 has the potential to be used as a lead compound for the design and development of new immunosuppressants for preventing graft rejection and treating autoimmune diseases.